PEMBUATAN SISTEM INFORMASI PENILAIAN SISWA/I DENGAN MENGGUNAKAN VISUAL BASIC .NET PADA SMA NEGERI 1 RONGGURNIHUTA - Sastra Wandi Nduru; Lasrida Sigalingging; Robin Antoni Sianipar; Harmoko Lubis; Maslan M.R. Sihombing; Dinaria br. Sembiring (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
In this activity, development are carried out, which builds the process of developing an assessment application system or what is called an e-report. This system was created and designed with an offline system so that this system is quite easy to use by users, the subjects in this study were students of SMA Negeri 1 Ronggurnihuta. This research aims to produce automated report cards from conventional to electronic methods, provide e-report results that can avoid manual writing errors, and make teacher performance easier to input and update report cards. The research was conducted to produce an e-report system application product that is more current in its processing using Visual Basic Net.2010 with a model and appearance that is quite attractive with various conveniences in its application. The system designed can produce report cards that have been automated to become value reports or report cards that are effective, efficient, and practical in their use.